2003
DOI: 10.1002/marc.200300051
|View full text |Cite
|
Sign up to set email alerts
|

Probing Nanoscale Polymer Interactions by Forced‐Assembly

Abstract: When two immiscible polymers are brought into intimate contact, highly localized mixing of polymer chains creates an “interphase” region. Materials that are entirely interphase are fabricated by forced‐assembly using layer‐multiplying coextrusion to form assemblies of thousands of nanolayers. Analysis of the interphase materials with conventional methods of polymer analysis confirms certain theoretical predictions for the first time. The unique properties of the new interphase materials result from lower free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
133
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(138 citation statements)
references
References 18 publications
4
133
1
Order By: Relevance
“…In addition, these results indicate that multilayer films with layer thicknesses at or near the nanoscale [63][64][65] and nanostructured or quasi-nanostructured polymer blends with substantial interfacial area [66][67][68] have the potential for properties that are strongly modified from those expected on the basis of the behavior of bulk, neat polymer or thin films of individual polymers. Bilayer and multilayer experiments employing fluorescence dyes in one layer provide a particularly sensitive method for characterizing novel behavior associated with nanostructured multilayer films and nanostructured blends, and further studies are underway.…”
Section: Ellison and Torkelson Indicating The Large Negative Values Ofmentioning
confidence: 87%
“…In addition, these results indicate that multilayer films with layer thicknesses at or near the nanoscale [63][64][65] and nanostructured or quasi-nanostructured polymer blends with substantial interfacial area [66][67][68] have the potential for properties that are strongly modified from those expected on the basis of the behavior of bulk, neat polymer or thin films of individual polymers. Bilayer and multilayer experiments employing fluorescence dyes in one layer provide a particularly sensitive method for characterizing novel behavior associated with nanostructured multilayer films and nanostructured blends, and further studies are underway.…”
Section: Ellison and Torkelson Indicating The Large Negative Values Ofmentioning
confidence: 87%
“…74,75 The scientifically and technologically important interphase between two immiscible polymers is probed with assemblies of thousands of alternating layers of two glassy polymers, with the individual layer thickness on the nanometer size scale of the interphase. 76,77 By sensing the composite nature of the assembly, gas transport becomes a primary method for extracting the dimension and other fundamental characteristics of the interphase. Nanolayer assemblies of crystalline polymers are also fabricated by layer-multiplying coextrusion.…”
Section: New Opportunities For Gas Transport As a Structure Probementioning
confidence: 99%
“…In pioneering work, Baer and coworkers have used this "forced assembly" technique and have shown that immiscible polymer pairs and filled/unfilled polymers can be forced to combine into a unique multilayer structure, accompanied with interesting confined crystallization effects [19], gas barrier properties [20], and optical properties [21]. In addition, Koets et al report the toughening of immiscible amorphous polymer pairs by multilayer coextrusion [22].…”
Section: Introductionmentioning
confidence: 99%